Exploring High School Students’ Understanding of Physical Quantities and Derivatives Through a Narrative Questionnaire: A Study at SMA 2 Merangin - Azzahran Arrusdi Askar; Fauzan Sulman; Aminah Zb (JUPE : Jurnal Pendidikan Mandala, 2026)
This study discusses how students at SMA 2 Merangin understand physics concepts, particularly those related to quantities and derivatives. The background of this study arose because many high school students still have difficulty understanding physics lessons, especially when learning about quantities and derivatives. The purpose of this study is to see how well students understand this material. The method used was a descriptive qualitative approach with field studies, which focused on students' experiences and views on how they learn. The population studied was all 30 students in grade X, and a sample of 15 students was taken so that the data obtained could represent the conditions of the class. Data collection was conducted using a questionnaire with 10 questions using a Likert scale to find out students' views, level of understanding, learning problems, and the influence of internal and external factors on their understanding. The results of this study show that many students have difficulty relating the concepts of quantities and derivatives, especially when given irrelevant examples. This study concluded that there is a need for innovation in teaching methods, reinforcement of basic concepts, and increased use of visual media and simple experiments to help students better understand the concepts of magnitude and derivatives.